Підвищення цифрової компетентності педагога засобами інформаційно-комунікаційних технологій - Ємчук, Тетяна Володимирівна (Academic notes. Series: Pedagogical Sciences. Kropyvnytskyi: EPC of Volodymyr Vynnychenko Central Ukrainian State Pedagogical University, 2022)
The article analyzes the impact of information and communication technologies of education on the transformation of digital competence of teachers. The necessity of formation of digital competence of teachers at conditions of wide introduction of information and communication technologies in educational process is proved. The place and role of application of information and communication technologies in the organization of educational process, and also use of computers, multimedia and information technologies which influence improvement of motivation and individualization of training are analyzed. Among them are the growth of such processes as attention, memory, thinking, imagination, speech, developed sense of composition. Thus, the use of computers, interactive equipment will affect the growth of knowledge and skills of students, which will lead to the development of intellectual and motivational nature. This in turn will change the procedure for providing educational services, make classes more visual and interesting. The teacher will act as a creative leader, will guide the transition of students from static to dynamic knowledge. That is, the structure of classes with the use of information and communication technologies will change the very essence of the educational process, turn it into communication, where the roles of teacher and educator are balanced. The analysis of digital competence of teachers acquires special relevance in the article. A survey was conducted in which 122 teachers of secondary and higher education institutions of Ukraine took part. The research methodology was based on the European Digital Competence Framework for Educators (DigCompEdu). As a result, the level of their competence in working with digital technologies is analyzed. Today, the teaching profession is facing rapidly changing demands. This requires educators to develop digital competence. It is not enough for a teacher to have only basic skills in the field of information technology. In our opinion, digital competence is an important component of the professional competence of a modern teacher.
NCREASING THE DIGITAL COMPETENCE OF THE TEACHER BY MEANS OF INFORMATION AND COMMUNICATION TECHNOLOGIES
Keywords: цифрова компетентність учителя; інформаційно-комунікаційні технології; цифрові засоби